Correlations between Percolation Threshold, Dispersion State, and Aspect Ratio of Carbon Nanotubes - Li, J.; Ma, P.C.; Chow, W.S.; To, C.K.; Tang, B.Z.; Kim, J.
Critical factors that determine the percolation threshold of carbon nanotube (CNT)-reinforced polymer nanocomposites are studied. An improved analytical model is developed based on an interparticle distance concept. Two dispersion parameters are introduced in the model to correctly reflect the different dispersion states of CNTs in the matrix-entangled bundles and welldispersed individual CNTs. CNT-epoxy nanocomposites with different dispersion states are fabricated from the same constituent materials by employing different processing conditions. The corresponding percolation thresholds of the nanocomposites vary over a wide range, from 0.1 to greater than 1.0 wt